Inhibition of osteoclast generation: a novel function of the bone morphogenetic protein 7/Osteogenic Protein 1 - Maurer, Thomas B.; Zimmermann, Gerald; Maurer, Susanne; Stegmaier, Sabine; Wagner, Christof; Hänsch, Gertrud Maria (Mediators of inflammation, 2012)
Monocytes have the potential to differentiate to either macrophages, dendritic cells, or to osteoclasts. The microenvironment, particularly cytokines, directs the monocyte differentiation. Receptors of NFB (RANK) ligand, tumor necrosis factor (TNF) , or interleukin- (IL-) 8 have be identified as inducers of osteoclastogenesis, whereas others, such as IL-10 or transforming growth factor (TGF) inhibit osteoclast generation or induce differentiation towards a dendritic cell type. We now describe that bone morphogenetic protein (BMP) 7/osteogenic protein- (OP-) 1 inhibited the differentiation of human CD14